THE USE OF WATTPAD TO INCREASE STUDENTS READING SKILL AT FIRST GRADE STUDENTS OF SMPN 2 SUNGGUMINASA - Putra, Guruh Yusuf; Ul Haq, Muh. Zia; Hafid, Hilda (FKIP Unismuh Makassar, 2024)
This study investigated the effects of incorporating Wattpad, an online storytelling platform, on students' literal, interpretative, and reading comprehension skills. A total of 22 students participated in the study, and their comprehension abilities were assessed through pre-test and post-test scores. The findings revealed significant improvements in students' comprehension skills across all three categories after the intervention. In terms of literal comprehension, the majority of students initially struggled with understanding explicit information but demonstrated noteworthy progress in the post-test. Similarly, students exhibited enhanced interpretative comprehension skills, with increased ability to infer implicit meanings. Moreover, students' reading comprehension abilities notably improved, as reflected in higher scores and a reduced percentage of students in lower score ranges. These findings highlight the potential benefits of integrating Wattpad as a tool for enhancing students' comprehension skills and engaging them in reading activities. Further research is warranted to explore the long-term effects and optimal instructional strategies for utilizing Wattpad in promoting comprehensive literacy development among students.